Compromised campus : the collaboration of universities with the intelligence community, 1945-1955 - Diamond, Sigmund (Oxford University Press, 1992)
Examines the role of the FBI in dealing with American universities regarding loyalty matters. The author has used the Freedom of Information Act to uncover instances of FBI illegal activities in this area.